LEGAL ANALYSIS OF COPYRIGHT REGULATIONS IN DEALING WITH GENERATIVE ARTIFICIAL INTELLIGENCE - Yohanes Yoris (Faculty of Law, Widya Gama University, Malang, 2026)
This study aims to analyze legal regulations related to the use of generative artificial intelligence (AI) in intellectual property rights (IPR), as well as the legal implications that arise, and government efforts to regulate them. The type of research used is normative legal research, which examines law as written norms in legislation as well as the principles and doctrines that develop in the legal community. The results of the study indicate that regulations related to the use of generative AI in IPR remain unclear, especially regarding copyright ownership, patents, and data protection. This lack of norms creates legal uncertainty that hinders justice for injured parties. The Indonesian government, despite issuing Circular Letter of the Minister of Communication and Information Technology Number 9 of 2023 concerning the ethics of AI use, has not fully addressed the lack of norms regarding the legal standing and accountability of AI in criminal law. Based on these findings, the following recommendations are proposed: 1) The government needs to formulate clear regulations regarding the use of AI to provide legal certainty, protection, and justice for victims, and 2) The need for the establishment of a supervisory agency to ensure that the use of AI is not misused in criminal acts.